Two-positional (Antarctica-Ukraine) monitoring of global electromagnetic resonances of the Earth - Koloskov, A. V.; Baru, N. A.; Budanov, O. V.; Paznukhov, V. E.; Yampolskiy, Yu. M. (Ukrainian Antarctic Journal, 2012)
The Schumann Resonance (SR) and Ionospheric Alfven Resonance (IAR) are the global resonance systems which form the electromagnetic surrounding of the Earth in ULF-ELF waveband. Studying of SR and IAR is of a great importance for modern geophysics, allowing researches both the properties of the resonances sources (worldwide thunderstorm activity) and the characteristics of the propagation medium of the signals (ionosphere and magnetosphere of the Earth). The results of the investigations of resonances may clarify the problem of global climate changes and help to track the variability of the space weather. Therefore the patrol of the SR and IAR signals was started at Ukrainian Antarctic Station (UAS) in 2002. At the same time the global nature of the resonances require realizing the spaced sensor measurements. That’s why since 2007 the Low Frequency Observatory (LFO) of the IRA NASU in Ukraine is used as a second observation point. In the paper the hardware and software of the measuring complexes together with the techniques of collective acquisition and processing of the data from UAS and LFO are presented. The morphological features of resonance signals determined from the data of the long-term two-position monitoring at UAS and LFO are analyzed. The results of the evaluation of the diurnal and seasonal behavior of the activity of main worldwide centers of thunderstorms are presented. The perspectives for further improvement of the facilities and increasing the number of observation points are discussed.